2013
DOI: 10.1128/jcm.00680-13
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter Study Evaluating the Vitek MS System for Identification of Medically Important Yeasts

Abstract: The optimal management of fungal infections is correlated with timely organism identification. Matrix-assisted laser desorption ionization-time of flight (MALDI-TOF) mass spectrometry (MS) is revolutionizing the identification of yeasts isolated from clinical specimens. We present a multicenter study assessing the performance of the Vitek MS system (bioMérieux) in identifying medically important yeasts. A collection of 852 isolates was tested, including 20 Candida species (626 isolates, including 58 C. albican… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
56
0
7

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(66 citation statements)
references
References 36 publications
3
56
0
7
Order By: Relevance
“…The present study is the first to evaluate the performance of the Vitek MS v2.0 system for the identification of invasive yeast isolates in China and only the second reported study of the Vitek MS v2.0 system for yeast identification. Our results are comparable to findings from the previous single Vitek MS v2.0 system study, where Ͼ96% of the 852 isolates were correctly identified to the species level, 2.8% were not identified, and 0.6% were misidentified (23).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The present study is the first to evaluate the performance of the Vitek MS v2.0 system for the identification of invasive yeast isolates in China and only the second reported study of the Vitek MS v2.0 system for yeast identification. Our results are comparable to findings from the previous single Vitek MS v2.0 system study, where Ͼ96% of the 852 isolates were correctly identified to the species level, 2.8% were not identified, and 0.6% were misidentified (23).…”
Section: Discussionsupporting
confidence: 81%
“…Several studies have evaluated the performance of the Vitek MS system with database version 1.0 in yeast identification (20)(21)(22). However, there is only one reported study that evaluated the performance of the Vitek MS system with database v2.0 (incorporating 755 species, including 645 bacterial and 110 fungal taxa) for yeast identification (23). In addition, there have been no studies that evaluated the application of the Vitek MS v2.0 system in a large fungal surveillance program such as CHIF-NET where a diverse range of yeasts are encountered.…”
mentioning
confidence: 99%
“…The use of matrixassisted laser desorption ionization-time of flight mass spectrometry (MALDI-TOF MS) for the rapid identification of clinical yeast and mycobacterial isolates has been evaluated in some studies (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). However, there has been a limited number of direct comparison studies focusing on the performance of the two MALDI-TOF systems to rapidly identify yeast and mycobacterial clinical isolates (26)(27)(28).…”
mentioning
confidence: 99%
“…T o date, literature-based evidence has accumulated with respect to the reliability of matrix-assisted laser desorption ionization-time of flight mass spectrometry (MALDI-TOF MS) for the identification of yeast isolates in diagnostic clinical microbiology laboratories (1)(2)(3)(4)(5)(6)(7)(8)(9)(10). As already shown with bacteria, MALDI-TOF MS identifies yeasts with rapidity, accuracy, and superiority over conventional phenotypic methods (for review, see references [11][12][13][14][15].…”
mentioning
confidence: 99%